MicroRNA-150 Deletion from Adult Myofibroblasts Augments Maladaptive Cardiac Remodeling Following Chronic Myocardial Infarction - Satoshi Kawaguchi; Marisa N. Sepúlveda; Jian-peng Teoh; Taiki Hayasaka; Bruno Moukette; Tatsuya Aonuma; Hyun Cheol Roh; Meena S. Madhur; Il-man Kim (Biomolecules)
MicroRNA (miR: small noncoding RNA)-150 is evolutionarily conserved and is downregulated in patients with diverse forms of heart failure (HF) and in multiple mouse models of HF. Moreover, miR-150 is markedly correlated with the outcome of patients with HF. We previously reported that systemic or cardiomyocyte-derived miR-150 in mice elicited myocardial protection through the inhibition of cardiomyocyte death, without affecting neovascularization and T cell infiltration. Our mechanistic studies also showed that the protective roles of miR-150 in ischemic mouse hearts and human cardiac fibroblasts were, in part, attributed to the inhibition of fibroblast activation via the repression of multiple profibrotic genes. However, the extent to which miR-150 expression in adult myofibroblasts (MFs) modulates the response to myocardial infarction (MI) remains unknown. Here, we develop a novel 4-hydroxytamoxifen-inducible MF-specific miR-150 conditional knockout mouse model and demonstrate that the mouse line exhibits worse cardiac dysfunction after MI. Our studies further reveal that miR-150 ablation selectively in adult MFs exacerbates cardiac damage and apoptosis after chronic MI. Lastly, MF-specific miR-150 deletion in adult mice promotes the expression of proinflammatory and profibrotic genes as well as cardiac fibrosis following chronic MI. Our findings indicate a key protective role for MF-derived miR-150 in modulating post-MI responses.